Positivity to p-ANCA in patients with status epilepticus - Ferlazzo, Edoardo (BioMed Central, 2014)
BACKGROUND: Status epilepticus (SE) may occur in the setting of several internal or neurologic diseases. Anti-neutrophilic cytoplasmic antibodies (ANCA) are a group of Ig that may be observed in patients with different autoimmune disorders but are particularly associated with systemic vasculitis named ANCA-associated-vasculities (AAV). We herein report 3 patients with SE and positivity to p-ANCA. CASE PRESENTATION: One patient had a catastrophic evolution and died 5 months after disease onset. The other two patients had a good outcome and remained seizure-free at 30 months and 5 years of follow-up respectively. CONCLUSION: This report highlights the importance of considering ANCA dosage in patients with SE of unclear origin.